2015
DOI: 10.1016/j.jacc.2014.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Transcutaneous Electrical Vagus Nerve Stimulation Suppresses Atrial Fibrillation

Abstract: BACKGROUND Transcutaneous low-level tragus electrical stimulation (LLTS) suppresses atrial fibrillation (AF) in canines. OBJECTIVES We examined the antiarrhythmic and anti-inflammatory effects of LLTS in humans. METHODS Patients with paroxysmal AF who presented for AF ablation, were randomized to either 1 hour of LLTS (n = 20) or sham control (n = 20). Attaching a flat metal clip onto the tragus produced LLTS (20 Hz) in the right ear (50% lower than the voltage slowing the sinus rate). Under general anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
200
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(220 citation statements)
references
References 37 publications
10
200
1
9
Order By: Relevance
“…In recent years the major sites of interest for delivering electrical stimulation to the ABVN have been the inner surface of the tragus (Busch et al, 2013;Clancy et al, 2014;Kraus et al, 2013;Stavrakis et al, 2015;Weise et al, 2015;Zhou et al, 2016), the concha (Ay et al, 2015b;Fang et al, 2015;He et al, 2013b;Liu et al, 2013), and the cymba concha (Frangos et al, 2015;Kreuzer et al, 2014). In parallel with these ear studies, a method said to allow non-invasive cervical vagus nerve stimulation through the skin of the neck has also been developed and is under investigation in patients with cluster headache (Nesbitt et al, 2015) and migraine (Barbanti et al, 2015).…”
Section: Cardiac Effects Of Tvnsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years the major sites of interest for delivering electrical stimulation to the ABVN have been the inner surface of the tragus (Busch et al, 2013;Clancy et al, 2014;Kraus et al, 2013;Stavrakis et al, 2015;Weise et al, 2015;Zhou et al, 2016), the concha (Ay et al, 2015b;Fang et al, 2015;He et al, 2013b;Liu et al, 2013), and the cymba concha (Frangos et al, 2015;Kreuzer et al, 2014). In parallel with these ear studies, a method said to allow non-invasive cervical vagus nerve stimulation through the skin of the neck has also been developed and is under investigation in patients with cluster headache (Nesbitt et al, 2015) and migraine (Barbanti et al, 2015).…”
Section: Cardiac Effects Of Tvnsmentioning
confidence: 99%
“…In patients with paroxysmal atrial fibrillation, 1 hour of low level tVNS under general anaesthesia significantly decreased atrial fibrillation duration (induced by burst atrial pacing), significantly increased atrial fibrillation cycle length and significantly decreased systemic levels of the inflammatory factors tumour necrosis factor alpha (TNF-alpha) and C-reactive protein (Stavrakis et al, 2015). Meanwhile, in patients with chronic heart failure and severe left ventricular dysfunction, a 15 day course of daily tVNS sessions (increasing duration per session, up to 30 minutes) on the internal surface of the auricle significantly increased distance of a 6 minute walk test and improved the clinical condition in the majority of patients.…”
Section: Cardiac Effects Of Tvnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Are there alternatives that could be added to the armamentarium of methodologies to treat the various forms of AF? Recent experimental 30 and clinical 31 studies have demonstrated that low-level nerve stimulation (that does not slow the heart rate and is nonsentient) applied at the auricular branch of the vagus nerve (the tragus of the outer ear) can consistently suppress AF. Other alternative therapies that have been proposed for the treatment of AF include acupuncture 32 and Yoga.…”
Section: Article See P 1276mentioning
confidence: 99%
“…Similarly, Antonio et al used TNS to modulate activity within the auricular branch of the vagus nerve and treat spontaneous cardiac baroreflex sensitivity [7]. Additionally, transcutaneous vagus nerve stimulation has been demonstrated to reduce atrial fibrillation in humans [144].…”
Section: Transcutaneous Nerve Stimulatorsmentioning
confidence: 99%